2011
DOI: 10.17221/71/2010-pps
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal effects of thiacloprid, acetamiprid, lambda-cyhalothrin and alpha-cypermethrin on Bruchus pisorum L. (Coleoptera: Chrysomelidae) eggs

Abstract: The effects of two pyrethroid (lambda-cyhalothrin, alpha-cypermethrin) and two neonicotinoid (acetamiprid, thiacloprid) insecticides on B. pisorum L. eggs were compared under field conditions in the Czech Republic in 2005–2007. The main objective of the study was to find out what real effects can be expected from the available insecticides registered in Europe when applied at the time of the first egg occurrence on lower pods. In general, the rates of Bruchus pisorum egg (+ first instar larvae) survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…However, egg monitoring on pods is complicated and very time-consuming for farmers, so the spray timing is often incorrect and the control is generally poor (Ward & Smart 2011). Moreover, even if the spray timing is correct, the effects of commonly available insecticides (pyrethroids, neonicotinoids) are often unsatisfactory (Matłosz & Kaniuczak 1997;Bruce et al 2011;Seidenglanz et al 2011). Problems with controlling this insect pest imply lost opportunities for growers in lucrative markets for doi: 10.17221/122/2015-CJGPB seed stock production and human consumption (the latter is not the case for CZ growers) due to crop rejection on standards of quality.…”
mentioning
confidence: 99%
“…However, egg monitoring on pods is complicated and very time-consuming for farmers, so the spray timing is often incorrect and the control is generally poor (Ward & Smart 2011). Moreover, even if the spray timing is correct, the effects of commonly available insecticides (pyrethroids, neonicotinoids) are often unsatisfactory (Matłosz & Kaniuczak 1997;Bruce et al 2011;Seidenglanz et al 2011). Problems with controlling this insect pest imply lost opportunities for growers in lucrative markets for doi: 10.17221/122/2015-CJGPB seed stock production and human consumption (the latter is not the case for CZ growers) due to crop rejection on standards of quality.…”
mentioning
confidence: 99%
“…There was insignificant difference with pre and post treatment application egg counts; though statistically non-significant, there was a clear reduction with treatments. Seidenglanz et al (2011) observed that pyrethroid insecticides were more effective compared to the neonicotinoids. As such the number of died eggs might be compensated by the newly oviposited eggs and, egg numbers before and after treatment application probably balanced each other.…”
Section: Resultsmentioning
confidence: 99%
“…Rychlik, Telefon, and Viktoria). This species still remains pestilential because of uncertainty about its field control, even with the modern generation of insecticides (Seidenglanz et al 2011). Additionally, the fumigation of the Bruchid infested pea seeds by phosphine in stores must be performed with care and under hermetic conditions to ensure full efficacy (Williams & Whittle 1996).…”
Section: Pests Of Seeds In the Czech Republicmentioning
confidence: 99%